PHILOSOPHY OF PERENNIALISM AND ITS RELEVANCE TO CONTEMPORARY ISLAMIC EDUCATION - Jamaludin Malik (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
Perennialis is born as a reaction to progressive education. Perennialism opposesthe progressive view which emphasizes change and something new. Perenialism view the world situation today is full of chaos, uncertainty, and disorder, especially in moral, intellectual and socio-cultural life. Aspects of the study of the application of perennialism in Islamic religious education include the purpose of education as an effort to inherit culture and maintain the nature of students, learning material according to perennialism, curriculum development and selection of learning methods in Islamic religious education. The idea of ​​perennialism that tends to be regressive, traditionalist and conservative causes the application of perennialism in Islamic education to have two sides, on the one hand it can have a good effect and on the other hand it has a negative impact.